Mesenchymal stem cell-derived exosomes carrying miR-486-5p inhibit glycolysis and cell stemness in colorectal cancer by targeting NEK2 - Facai Cui; Yu Chen; Xiaoyu Wu; Weifeng Zhao (BMC Cancer)
Abstract Colorectal cancer (CRC) is a major global concern. Mesenchymal stem cell-derived exosomes (MSC-EXOs) have demonstrated efficacy as a therapeutic approach for colorectal cancer. However, the precise mechanism by which MSC-EXOs treat colorectal cancer remains unclear. Human umbilical cord (hUC)-MSC-EXOs were isolated and identified. Cell Counting Kit-8 (CCK-8), Transwell, and colony formation assays were used to assess the activity of CRC cells. Glucose consumption, lactic acid production, and extracellular acidification rate (ECAR) were measured to assess glycolytic activity. Cell stemness was assessed using a sphere-formation assay. Furthermore, MSC-exosomal microRNAs (miRNAs) in CRC tissues were analyzed using the EVmiRNA database, and aberrantly expressed miRNAs in CRC cells were obtained from the Gene Expression Omnibus (GEO) database. The binding relationship between miR-486-5p and the never in mitosis gene A-related kinase 2 (NEK2) was predicted using the Starbase database and validated through RNA binding protein immunoprecipitation (RIP) and dual luciferase assays. These results showed that hUC-MSC-EXOs inhibited the proliferation and metastasis of CRC cells. Moreover, glycolysis and stemness abilities of CRC cells also decreased after treatment with hUC-MSC-EXOs. miR-486-5p was found to be enriched in hUC-MSC-EXOs and significantly downregulated in CRC cells. miR-486-5p directly bound to NEK2. Overexpression of NEK2 reversed the inhibitory effect of miR-486-5p on CRC cell glycolysis and stemness. Our study highlights that hUC-MSC-EXO miR-486-5p inhibits glycolysis and cell stemness in CRC by targeting NEK2. This finding offers compelling evidence supporting the potential application of hUC-MSC-EXOs in the treatment of CRC.